Kinematics and P-T-t evolution in hot collisional frameworks a comparison between a Neoproterozoic and a Phanerozoic large Hor orogens - Silva, Beatriz Yuri Benetti (2022)
Large hot orogens (LHO) are characterized by an increase in heat the production and thickness of the lithosphere. The increase in heat production, related to the accretion of highradiogenic continental crust, leads to middle and lower crust partial melt and consequently decreases their strength. The gradient in lithostatic pressure between the thickened crust and its foreland will result in the ductile flow of the partially molten and weakened middle and lower crust. The rocks from the orogen wedge hinterland are constituted by crustal material detached from the subducted lithosphere, accreted, and stored within the orogenic system. Therefore, the hinterland rocks are able to record pressure (P) and temperature (T) changes during the orogen development as well as its kinematics history. In order to explore the lithosphere modifications during this mature stage of the continental collision, it was investigated hinterland sections of two large hot orogens, the Himalayan Orogen and the Southern Brasilia Orogen. In the Himalayan Orogen, a transect of the Greater Himalayan Sequence was described in the Alaknanda valley, localized in the Garhwal region, NW India. A P-T-t-D study was addressed for these rocks and allowed us to reveal the occurrence of a newly described high-temperature shear zone, called Badrinath Shear Zone, within the Greater Himalayan Sequence. The occurrence of a high-temperature shear zone, the contrast in exhumation onset (ca. 3 Ma), and the apparent geothermal gradient difference between the Lower and Upper Greater Himalayan Sequence set up a tectonic-metamorphic discontinuity inside the Greater Himalayan Sequence in the study area. The Badrinath Shear Zone characteristics match with the High Himalayan Discontinuity geological features and, thus is here suggested that it represents its prolongation in Garhwal Himalaya (NW India). The Badrinath Shear Zone is interpreted as the High Himalayan Discontinuity branch in NW Himalaya. It corroborates with the regional extent of the High Himalayan Discontinuity accomplishing an important role during the GHS exhumation. Such findings support that the deformation was accommodated by high-temperature shear zones during progressive midcrust exhumation from top to bottom in the GHS, as highlighted by the model in-sequence shearing. In the Southern Brasilia Orogen an exposition of the Andrelândia Nappe System, localized in Pouso Alto county, southeast Brazil, was studied. In the area, the three structural levels of the nappe system crop out from top to bottom: the Pouso Alto, Liberdade, and Andrelândia Nappes. The obtained P-T-t-D results indicate an in-sequence propagation of the nappes stack toward the Andrelândia Nappe System bottom. The spread of ages within the orogen would represent different periods in which each nappe from the system attained prograde and retrograde metamorphism. This new dataset reinforces the idea that Southern Brasilia Orogen evolved by the progressive evolution of the continental collision between the Paranapanema and São Francisco cratons. Furthermore, the provided data from the Pouso Alto Nappe records HP-UHT metamorphic conditions for the first time within the Southern Brasilia Orogen. The P-T data indicate that this rock was part of the continental subduction channel and reached crustal depths of ca. 70 km, corresponding to the interface between the lower crust and lithospheric mantle in a double-thickened crust. It is suggested that the UHT metamorphic condition was attained by combining heat production elements accumulation and minor mantle heat flow. The previous melt-weakened rocks from the Pouso Alto Nappe onset their flow outward likely driven by the gravitational force. Lastly, it is proposed that the exhumation onset would record the transition from a wedge-shaped orogenic belt to an orogenic plateau during the continental collision development. The results from this thesis indicate that the Large Hot Orogens can display a wedgeshaped (i.e., Himalayan Orogen) and fold-nappe (i.e., Southern Brasilia Orogen) hinterland geometry. The hinterland can be constituted by middle (i.e., Himalayan Orogen) and/or lower (i.e., Southern Brasilia Orogen) crustal rocks. The geothermal gradients vary within the Barrovian field, and the perturbed isotherms remained in a time range of 35 to 50 Ma until they started re-equilibrating. In both of the study cases, they evolved by progressive metamorphism and deformation owing to a single continental collision event. Folds and shear zones played a first-order role in accommodating ductile deformation during the assembly and the exhumation of the middle and lower crust. The studied examples of large hot orogens followed an in-sequence propagation pattern from the hinterland toward the foreland, and it is suggested that their exhumation was driven mainly by the gravitational force.